The Effect of Reservation Wages on The Duration of Job Search among Young Workforce in Indonesia - Mutiara Shinta Andini (Jurnal Budget : Isu dan Masalah Keuangan Negara, 2025)
This study analyzes the effect of reservation wages on the duration of job search for young people in Indonesia using SAKERNAS data. Reservation wages are defined as the minimum wage level that individuals are willing to accept to enter the job market, while the duration of the job search is measured from the length of time it takes to find a job until obtaining the first job. The method used is Ordinary Least Squares (OLS) with robust standard errors to overcome heteroscedasticity. The results showed that the higher the reservation wage, the longer the duration of the job search, indicating that excessively high wage preferences can prolong unemployment. Control variables such as type of education, work experience, gender, and location of residence also had a significant effect on the duration of the job search. These findings provide a new understanding of the dynamics of the transition of the young workforce in Indonesia and the importance of policies that encourage labor market information and skill improvement to reduce wage expectation mismatch.